Efektifitas Pelaksanaan Sertifikasi Tanah Wakaf Di Kecamatan Mojoroto Kota Kediri - Muhammad Saiful Bahri; Abbas Sofwan Matlail Fajar (JOURNAL of LEGAL RESEARCH, 2022)
The obligation to submit an application for a waqf land certificate is regulated in Government Regulation Number 25 of 2018 Article 51 A Paragraph (1) that "Institutions or parties who will use waqf land are required to submit applications for waqf certificates on behalf of Nazhir for replacement land to the local land office no later than 10 (ten) working days after obtaining written permission from the Minister or Head of Regional Office as referred to in Article 51”. This research was conducted to find out what is the function of certifying waqf land in Mojoroto District, Kediri City? What is the process of certifying waqf land in Mojoroto District, Kediri City and the obstacles it faces? How effective is the implementation of waqf land certification in Mojoroto District, Kediri City?